PENGEMBANGAN MEDIA PEMBELAJARAN BUKU ELEKTRONIK (E-BOOK) UNTUK MATA PELAJARAN EKONOMI DENGAN POKOK BAHASAN PERDAGANGAN INTERNASIONAL KELAS XI IIS SMA NEGERI 1 TALUN BLITAR - Chusnatul Zulva Wavirotin; Yohanes Hadi S. (Universitas Negeri Malang, 2016)
The more rapidly technological development enables to develop an attracted learning media. SMA Negeri 1 Talun has possesed a facility supports electronic based learning media usage. But during this time, the usage of electronic media has not been implemented maximally because teacher often used media, such as module or packet book and less attracted power-point more. International trading is one of subject matters must be studied by XI IIS grade students. International trading is one of subject matters presents text more, so if it is tought by using packet book or module will make students feel bored exactly. Because of that, a media was developed to share attractive visualization in wish to be able to increase motivation for students and to make students easy in comprehending international trading subject matter.This developmental research used ADDIE model adjusted to the kind of developed product. The validation was carried out through some steps, included of media expert and subject matter expert validation, and trial step. The results of validation and trial step of experiment showed a positive response and learning media had fulfilled very valid criteria to be used in learning. Keywords: Learning Media, E-Book, International Trading